Post Un-Lock From Territorial Vulnerabilities to Local Resilience - Brunetta, Grazia; Lombardi, Patrizia; Voghera, Angioletta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open access book builds a framework that holds together numerous open issues in territorial planning: from the understanding of territorial, landscape, environmental and climatic dynamics to the analysis of local vulnerabilities, to the use of modern survey techniques to support planning. What is the role of urban and regional planning in achieving the sustainable development goals of our communities considering the major issues posed by the COVID-19 pandemic in urban planning? And how do these medium- and long-term objectives interact with the needs that the emergency has given rise to? Post Un-Lock$1 (Bfrom territorial vulnerabilities to local resilience$1 (Baims to provide the reader with a useful key to understand how the COVID-19 pandemic can be seen as a catalyst for a restart based on the concepts of sustainability and resilience. In fact, the COVID-19 experience evidences the need to propose a planning system able to integrate multiple scales according to an interdisciplinary approach focused on in-depth knowledge of the territorial risks and vulnerabilities. Besides, with the contribution of the new technologies, it is able to rethink spaces on a neighbourhood scale, conceived as a "local resilience unit" that ensures the population high standards of safety, liveability, and accessibility to proximity services. In this view, planning is increasingly concerned about social aspects and the well-being of communities, supported by indicators and evaluation tools. With the proposal of the concept of local resilience unit, Post Un-Lock takes a step forward towards the definition of a new paradigm of local planning and a topic for urban regeneration.s
Part 1: The research -- Post-pandemic challenges. The role of local governance for territorial resilience -- Part 2: Topics -- Notes of spatial implications of Covid-19. Evidence from Piedmont Region, Italy -- The role of the minor hydrographic system in increasing the ecological network -- Ecosystem services and territorial resilience: The role of green and blue infrastructure -- Indicators and scenarios for sustainable development at the local level -- Towards neighborhoods as minimum units of resilience?- Part 3: Case studies -- NO2 concentrations and Covid-19 in local systems of North-West Italy -- The COVID-19 effects and the development process of Lanzo Valleys in a metro-mountain perspective -- Analysis of hydrogeological risks related to climate change: Testing the ClimeApp assessment tool on the Torino Nord Homogenous Zone -- From knowledge to land-use planning: Local resilient experience in the territory of the municipality of Mappano -- Space for rights. The school between urban standards and social innovation -- Part 4: Digital tools -- The 3D metric survey for the digital cartographic production to support the knowledge of the new Municipality of Mappano -- Sources and data for the analysis of the metropolitan territory with GIS tools -- Part 5: Lesson learned and perspectives -- Final remarks on the implementation of the post-pandemic city and the role of technology.
Keywords: Urban policy; Sustainability; Urban Policy; Sustainability